Association between Inactive-Gymnastics and ActiveGymnastics Elderly towards Cognitive Functions Measured by The Mini-Mental State Examination (MMSE) (Medico Legal Update, 2020)
Background : The decline of cognitive function is a problem that often experienced by the elderly.Objectives : to determine the role of elderly gymnastics towards cognitive function.Methods : A total of 50 elderly patients that fulfilled the inclusion and exclusion criteria in Kedurus village,Surabaya, from September to October 2013 were conducted. The cognitive function was examined usingThe Mini-Mental State Examination (MMSE) and the results were allocated to two groups: the case groupwith the MMSE score less than 26/30 while MMSE control group from 27/30.Results : During the study, 50 subjects were enrolled (25 case groups and 25 control groups). It was obtainedin case group that did inactive-gymnastics was 15 (60%) and active-gymnastics was 10 (40%), with P =0.047 and OR 3.188 (CI 0.99-10.17)Conclusion : There was no significant correlation between inactive-gymnastics elderly and activegymnastics towards cognitive function.